X-ray micro-computed tomography in willow reveals tissue patterning of reaction wood and delay in programmed cell death - Brereton, Nicholas James Beresford (BMC Plant Biol, 2015)
BACKGROUND: Variation in the reaction wood (RW) response has been shown to be a principle component driving differences in lignocellulosic sugar yield from the bioenergy crop willow. The phenotypic cause(s) behind these differences in sugar yield, beyond their common elicitor, however, remain unclear. Here we use X-ray micro-computed tomography (μCT) to investigate RW-associated alterations in secondary xylem tissue patterning in three dimensions (3D). RESULTS: Major architectural alterations were successfully quantified in 3D and attributed to RW induction. Whilst the frequency of vessels was reduced in tension wood tissue (TW), the total vessel volume was significantly increased. Interestingly, a delay in programmed-cell-death (PCD) associated with TW was also clearly observed and readily quantified by μCT. CONCLUSIONS: The surprising degree to which the volume of vessels was increased illustrates the substantial xylem tissue remodelling involved in reaction wood formation. The remodelling suggests an important physiological compromise between structural and hydraulic architecture necessary for extensive alteration of biomass and helps to demonstrate the power of improving our perspective of cell and tissue architecture. The precise observation of xylem tissue development and quantification of the extent of delay in PCD provides a valuable and exciting insight into this bioenergy crop trait. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12870-015-0438-0) contains supplementary material, which is available to authorized users.